Toluene alters the intrinsic excitability and excitatory synaptic transmission of basolateral amygdala neurons - Braunscheidel, Kevin; Okas, Michael; Woodward, John J. (Frontiers in Neuroscience, 2024)
Introduction Inhalant abuse is an important health issue especially among children and adolescents who often encounter these agents in the home. Research into the neurobiological targets of inhalants has lagged behind that of other drugs such as alcohol and psychostimulants. However, studies from our lab and others have begun to reveal how inhalants such as the organic solvent toluene affect neurons in key addiction related areas of the brain including the ventral tegmental area, nucleus accumbens and medial prefrontal cortex. In the present study, we extend these findings and examine the effect of toluene on electrophysiological responses of pyramidal neurons in the basolateral amygdala BLA, a region important for generating emotional and reward based information needed to guide future behavior. Methods Whole-cell patch-clamp electrophysiology recordings of BLA pyramidal neurons in rat brain slices were used to assess toluene effects on intrinsic excitability and excitatory glutamatergic synaptic transmission. Results Acute application of 3 mM but not 0.3 mM toluene produced a small but significant (~20%) increase in current-evoked action potential (AP) firing that reversed following washout of the toluene containing solution. The change in firing during exposure to 3 mM toluene was accompanied by selective changes in AP parameters including reduced latency to first spike, increased AP rise time and decay and a reduction in the fast after-hyperpolization. To examine whether toluene also affects excitatory synaptic signaling, we expressed channelrhodopsin-2 in medial prefrontal cortex neurons and elicited synaptic currents in BLA neurons via light pulses. Toluene (3 mM) reduced light-evoked AMPA-mediated synaptic currents while a lower concentration (0.3 mM) had no effect. The toluene-induced reduction in AMPA-mediated BLA synaptic currents was prevented by the cannabinoid receptor-1 antagonist AM281. Discussion These findings are the first to demonstrate effects of acute toluene on BLA pyramidal neurons and add to existing findings showing that abused inhalants such as toluene have significant effects on neurons in brain regions involved in natural and drug induced reward.